PERSEPSI KONSUMEN TERHADAP HIGIENE DAN SANITASI KAMAR PADA HOTEL ASTON KUPANG - Zakharia, Friend (TOURISM: Jurnal Travel, Hospitality, Culture, Destination, and MICE, 2020)
This study aims to determine consumer perceptions of room hygiene and sanitation at Hotel Aston Kupang. This type of research is a quantitative descriptive study with a survey approach. The research sample is 83 consumers who stay at Hotel Aston Kupang. Data collection techniques using questionnaires, observation, literature and documentation. The validity test uses the product moment correlation formula, while the reliability test uses the Cronbach Alpha formula with the reliability coefficient values ​​0.817 and 0.926. After describing the value with a Likert scale, the data were analyzed using quantitative descriptive techniques, namely methods that describe some data logically so that conclusions can be drawn and supported by average analysis to answer the problem formulation. Based on the results of the discussion and analysis of previous data, it can be concluded that consumer perceptions of hygiene are good, while consumer perceptions of room sanitation at Aston Hotel Kupang are very good.